2012
DOI: 10.2460/ajvr.73.10.1553
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the association between runt-related transcription factor 2 expression and intervertebral disk aging in dogs

Abstract: Results indicated that RUNX2 mRNA and protein expression in the NP are enhanced in aging intervertebral disks in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In addition, Runx2 may also be implicated in the progression of intervertebral disc aging and calcification in humans and CDBs, and this induction occurs prior to MMP‐13 expression (Rutges et al, ; Itoh et al, ), indicating that Runx2 plays an important role in IVD degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Runx2 may also be implicated in the progression of intervertebral disc aging and calcification in humans and CDBs, and this induction occurs prior to MMP‐13 expression (Rutges et al, ; Itoh et al, ), indicating that Runx2 plays an important role in IVD degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…To measure and normalize the MRI signal intensity of NP tissue, we determined the disc center‐to‐cerebrospinal fluid (DC:CSF) T2‐weighted signal intensity ratio, which was reported previously by Itoh et al (). For DC:CSF determination, the plane with the subjectively brightest discs on midsagittal T2‐weighted images was chosen, and regions of interest were selected centrally in the high‐signal area of each disc and in the free CSF region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have documented the BMP-induced stimulation of chondrogenesis and the regeneration of the extracellular matrix of the intervertebral disc (8,9), another study demonstrated no effect of BMPs in preventing the degeneration of the intervertebral disc, but demonsrated that it led to intervertebral disc calcification (10). The expression of runt-related transcription factor 2 (Runx2), a key transcription factor for chondrocyte hypertrophic differentiation (11), has been shown to be upregulated in the degenerative discs of dogs (12) and humans (13). Unlike dystrophic calcification, disc ossification is a positive osteogenic process associated with osteoblasts (14); however, the origin of osteogenic cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The adoptive scoring system was that described by Itoh et al [ 11 ]; cell counts were performed by 2 independent observers. More than 100 cells in each sample were examined to evaluate the proportion of cells that showed a positive reaction for NG2 proteoglycan.…”
mentioning
confidence: 99%